Drug Absorption Studies: In Situ, In Vitro and In Silico Models - Song, Im-Sook (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Book serves to highlight the mechanisms related to the low intestinal drug absorption, the strategies to overcome the obstacles or intestinal drug absorption, and in situ, in vitro, and in silico methodologies to predict to intestinal drug absorption. This Book presents a series of drug absorption studies and related technologies that predict intestinal permeation of drugs that govern the pharmacokinetic features of therapeutic drugs. It also contains the mechanistic understanding regarding the first-pass metabolism and intestinal efflux that modulate the pharmacokinetics of drug and suggest the formulation strategies to enhance the bioavailability of investigated drugs.